Investigation the change joint angle on antagonist muscle co-activation in isometric contraction - فریبرز هوانلو; مجتبی صالح پور; سید علی حسینی; سیروس شیخی (Shahid Beheshti University, 2014)
This study seeks to answer this question that the variations of muscle length or joint angular can change the rate of coactivation of antagonist muscle in isometric contraction? The subjects were 15 male students with average age 21.67-1.58, height 172.93+5.13an and weight 60.85±5.41kg All subjects were healthy and had no any history of pain or injury in arm, elbow and wrist. IEMG were taken from biceps and triceps with maximal voluntary contraction in 90-120 and 180 degree of elbow joint. Results showed that maximal voluntary contraction of elbow in 90° and 120° angle (P-0.001) were significantly increased in comparison with 180°. Whereas there were no significant difference between maximal voluntary contraction of elbow in 90° and 120° angle (P-0.516).The electrical activity of biceps and triceps in elbow angles of 90° (P=0.010) and 120° (P=0.002) were significantly greater than 180° (P=0.043). Also there were no significant difference between electrical activity of biceps and triceps in elbow angles of 90° (P-0.819) and 120° (P-0.202). Results indicate that other factors except joint angel would affect the research outcomes. Some researchers report differences in muscles recruitment patterns due to velocity of movement, amount and type of muscle work and force production. Joint angel has the most effect than other factors such as movement velocity. So Joint angel as a prominent factor in control of recruitment patterns of muscles should be noticed. It is important that when bodybuildings coach's sports teams want strengthen a particular muscle with respect to its importance in moving a given motion in a particular sport, that in this case to put the muscle at greatest burden, surrounding muscle and joint angles should be considered very carefully regulated.